Football Hooliganism, Fan Behaviour and Crime
XII, 312 p.
Keywords: Focusing on a number of contemporary research themes and placing them within the context of palpable changes that have occurred within football in recent years, this timely collection brings together essays about football, crime and fan behaviour from leading experts in the fields of criminology, law, sociology, psychology and cultural studies.